Electricity from Wind for Off-Grid Applications in Bangladesh: A Techno-Economic Assessment - Rahman, Md. Mustafizur; Baky, Md Abdullah Hil; Islam, A.K.M. Sadrul (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
Global GHG (greenhouse gas) emissions are increasing substantially and electricity sector is one of the key contributors to the world’s total GHG emissions. GHG emissions cause ozone layer depletion and global warming. Different policy regulation agencies are adopting regulations to reduce GHG emissions in various sectors. People already have started power generation from cleaner sources. Renewable energy sources can provide cleaner electricity. Bangladesh is a densely populated country and most of the country’s electricity is produced from natural gas and coal. The Bangladesh government has set a goal to utilize renewable energy for the production of 10% of its electricity by the year 2020. Bangladesh has a lot of isolated coastal areas which are not connected to the national grid which can be electrified by using abundant wind energy. In this study a techno-economic analysis has been conducted for an off-grid island of Bangladesh. The analysis was conducted by developing a data intensive model that calculates the generation cost of electricity from wind energy. The model also estimates the capital cost of the system. The model shows that electricity can be produced from wind energy at a cost of 0.57/kWh. The system’s capital cost was calculated to be 63,550.16.Article History: Received October 15th 2016; Received in revised form January 26th 2017; Accepted February 4th 2017; Available onlineHow to Cite This Article: Rahman, M.M., Baky, M.A.H, and Islam, A.K.M.S. (2017) Electricity from Wind for Off-Grid Applications in Bangladesh: A Techno-Economic Assessment. International Journal of Renewable Energy Develeopment, 6(1), 55-64.http://dx.doi.org/10.14710/ijred.6.1.55-64